ANALISIS PEMIDANAAN DALAM TINDAK PIDANA KEPABEANAN (STUDI KASUS NOMOR 1313/PID.SUS/2018/PN.JKT.UTR) - Dwiayu Agengsar (Jurnal Hukum Adigama, 2021)
The crime of smuggling is a form of crime that is very detrimental to the government in terms of state revenue and is very disturbing to the community in terms of economic stability. State consists of tax receipts, tax opening recepicts, and grants. The state of Indonesia as a legal state requires the realization of a flexible legal system based on Pancasila and the 1945 Constitusion which contains the principile of justice. This type of research aims to provide a systematic explanation of the rules governing a particular category of law. The method used is normative and the specifications are descriptive analytical, where with research, it can produce arguments which can then be useful to build a new mindset and provide something positive. The results of this study gave birth to an argument based on the facts that a country needs to accommodate an international trade but still adhere to the existing regulations in Indonesia law or other countries